On the Controlling Factors for Globally Extreme Humid Heat. Issue 23 (25th November 2021) - Raymond, Colin; Matthews, Tom; Horton, Radley M.; Fischer, Erich M.; Fueglistaler, Stephan; Ivanovich, Catherine; Suarez‐Gutierrez, Laura; Zhang, Yi
Abstract: Humid heat presents a major societal challenge through its impacts on human health, energy demand, and economic productivity, underlined by the projected emergence of conditions beyond human tolerance. However, systematic assessment of what drives the most extreme humid heat worldwide has been lacking. Here, we investigate factors determining the location and magnitude of humid‐heat extremes, framing our analysis around the four regions with the highest values: the southern Persian Gulf, north‐central Pakistan, eastern South Asia, and the western Amazon. We find that strong boundary‐layer moisture fluxes, together with stability that inhibits moist convection, explain well the timing and location of near‐surface humid‐heat extremes. These favorable conditions are achieved through regionally distinct factors, including shallow sea breezes in the Persian Gulf and large‐scale subsidence in eastern South Asia. Our results demonstrate some of the principal controls on the most intense humid heat, both globally and for particular regions and heat events. Plain Language Summary: Combinations of high temperatures and high humidity are a primary threat of climate change because they can be not only uncomfortable but deadly, and are growing rapidly in frequency and intensity. In this study, we present a general theory for where the most extreme such events occur and describe the precise meteorological conditions that favor them. We are therefore able to state with new confidence the reasons why extreme humid heat events take place where they do, and why. Our results also highlight the regional distinctions in the factors (such as winds or ocean temperatures) that contribute to these events, increasing the strength of the evidence that some regions are much more sensitive to certain factors than others—information that can be used to guide better forecasts as well as climate‐change projections. Key Points: A systematic assessment of humid‐heat hotspots reveals the dual importance of vertical stability and low‐level moisture sources These two conditions are achieved through markedly different meteorological processes and in markedly different geographical contexts Understanding the most extreme humid heat requires applying global principles to detailed regional analyses across space and time scales